2018
DOI: 10.1093/aob/mcy229
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the larger seed bank of an invasive shrub in non-native versus native environments by differences in seed predation and plant size

Abstract: Background and aims-Large, persistent seed banks contribute to the invasiveness of non-native plants, and maternal plant size is an important contributory factor. We explored the relationships between plant vegetative size (V) and soil seed bank size (S) for the invasive shrub (Ulex europaeus) in its native range and in non-native populations, and identified which other factors may contribute to seed bank variation between native and invaded regions.  Methods-We compared the native region (France) with two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…In terms of vegetative growth, our study showed an increase in height and leaf area for invasive gorse populations as compared to native populations in the early phases of the invasive process (seedling establishment) under warm conditions. This observation is in accordance with previous studies showing an increase in vegetative growth (Hornoy et al 2011) and reproductive output (Udo et al 2017;Bakker et al 2019) in introduced Ulex europaeus populations compared to native ones under non-limiting conditions.…”
Section: Traits and Seedling Performancesupporting
confidence: 93%
“…In terms of vegetative growth, our study showed an increase in height and leaf area for invasive gorse populations as compared to native populations in the early phases of the invasive process (seedling establishment) under warm conditions. This observation is in accordance with previous studies showing an increase in vegetative growth (Hornoy et al 2011) and reproductive output (Udo et al 2017;Bakker et al 2019) in introduced Ulex europaeus populations compared to native ones under non-limiting conditions.…”
Section: Traits and Seedling Performancesupporting
confidence: 93%
“…This study reported that salinity tolerance ability of U. europaeus is relatively less in its native range than when it is co-occurring with the invasive Acacia longifolia . Moreover, a comparative study done to compare the plant vegetative size and soil seed bank of U. europaeus in its native range and the invaded ranges showed that relatively larger seed banks in invaded ranges than on the native range (Bakker et al 2019 ). Larger maternal plant size, lower activity of seed predators, and higher soil fertility in the invaded areas were suggested as the potential reasons for these variations.…”
Section: Invasive and Native Common Gorse: A Comparative Analysismentioning
confidence: 99%